USING OF READING, ENCODING, ANNOTATING, AND PONDERING (REAP) TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION (A Classroom Action Research at Eighth Grade Students in MTSN 1 Kota Bengkulu in Academic years 2016) - Fera Zasrianita (Ta'dib, 2016)
AbstractThe researcher found the problem at MTSN 1 in the city of  Bengkulu at grade VIII I that students got difficulty in comprehending reading texts, and in understanding meanings of words in paragraphs, and teachers techniques  made the students bored. Therefore, the purpose of the research is to improve students’ reading comprehension through REAP techniques. The subject of the research is the students of  grade VIII I consisting of 27 students, 14 female students and 13 male students. The instruments of the research are reading tets, observation sheetteacher and the students, interview guide and that for documentary study.  The results of the research show that the  REAP teachniques are effective in improving the students’ reading comprehension. The students got involved directly and were able to cooperate with their peers during the teaching-learning process. The research was conducted in two cycles an the test was administered at the end of each cycle. From the average mean scores, it could be seen that there was improvement of the the students’ reading ability. In cycle I, the mean score was 70.5 and in cycle 2, it was 78.7,and at the Post assessment, it was  82.2. It means that the students’ mean scores has reached the research target. Thus, it can be concluded that REAPtechniques can improve the students’ readng comprehension. Kata Kunci: REAP (Reading, Encoding, Annotating, and Pondering) technique, Students’ reading comprehension